PENGUATAN EKONOMI KREATIF DAN PEMAHAMAN HUKUM BISNIS PADA USAHA COFFEE SHOP - Heni Risnawati; Tuti Nadhifah; Dian Rosita; Ria Etikasari; Sherly Nur Ekawati (Universitas Muhammadiyah Kudus, 2025)
This community service aims to increase the capacity of coffee shop business actors in Jrahi Tourism Village, Pati Regency, in building a sustainable creative economy by strengthening the understanding of business law and branding strategies. One of the fundamental problems faced by business actors is the weak understanding of the legal aspects of the business, especially in managing documents such as invoices, financial reports, and deeds of agreement. This not only poses a risk to business continuity, but also opens up opportunities for criminal acts such as embezzlement and forgery. In addition to the legal aspect, strengthening business identity through branding strategies is also an urgent need. Business actors are encouraged to create unique and authentic concepts by integrating local values and the potential of the natural scenery of Jrahi Village as part of the tourist attraction. Through counseling and mentoring, this activity has succeeded in increasing business actors' awareness of the importance of legality, business documentation, and the strategic value of differentiation and brand identity in building a professional, competitive, and local potential-based creative business.